Water scarcity, mountain deforestation and the economic value of water in a small-scale irrigation system: A case study in East Java, Indonesia - Budiman, Subhan Arif; Rondhi, Mohammad; Khasan, Ahmad Fatikhul; Peratama, Bagus; Rokhani, Rokhani; Suwandari, Anik; Ridjal, Julian Adam; Soemarno, Soemarno; PriJono, Sugeng; Soedarto, Soedarto (Quaestiones Geographicae, 2021)
The purpose of this study was to identify the willingness of farmers to pay for small-scale irrigation (SSI) and its determinants. Additionally, this study analysed the physical water availability in the study area using 16 years’ (2004-2019) historical data of streamflow, rainfall and forest cover change. A structured questionnaire was used to collect the data from 100 farmers. A contingent valuation method was employed to elicit farmers’ willingness to pay (WTP) for irrigation water. The results show that the average WTP of farmers is US 215.84/ha/year. It accounts for 20% of farm revenue and is almost 20 times the water fee in large-scale irrigation systems. The study area experienced significant deforestation in the last two decades suffering a decrease of 11.72% of forest cover. It decreases the amount of stored rainwater and decreases the streamflow causing water scarcity during the dry season. Farm size, farmer income, distance to a small dam and usage of water-pump are the significant determinants. The results indicate that water scarcity caused by poor infrastructure increases the economic value of water in a SSI system.